2013
DOI: 10.1016/j.neuroimage.2012.12.031
|View full text |Cite
|
Sign up to set email alerts
|

The structural connectome of the human brain in agenesis of the corpus callosum

Abstract: Adopting a network perspective, the structural connectome reveals the large-scale white matter connectivity of the human brain, yielding insights into cerebral organization otherwise inaccessible to researchers and clinicians. Connectomics has great potential for elucidating abnormal connectivity in congenital brain malformations, especially axonal pathfinding disorders. Agenesis of the corpus callosum (AgCC) is one of the most common brain malformations and can also be considered a prototypical genetic disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 55 publications
6
69
0
Order By: Relevance
“…We hypothesize, along with Owen et al (19), that the reported abnormal tracts, and perhaps additional ones yet to be described in the white matter of CD patients, result from abnormal molecular mechanisms taking place in the natural course of events in ontogenesis, leading to an anomalous network of connections in these subjects.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We hypothesize, along with Owen et al (19), that the reported abnormal tracts, and perhaps additional ones yet to be described in the white matter of CD patients, result from abnormal molecular mechanisms taking place in the natural course of events in ontogenesis, leading to an anomalous network of connections in these subjects.…”
Section: Discussionmentioning
confidence: 51%
“…Together, the longtime known Probst bundle (10), the more recently described sigmoid bundle (11), and the two novel aberrant midbrain and ventral forebrain tracts here reported make up the fundamental brain circuitry of CD subjects (12,19). We focused on the abnormal commissural interhemispheric bundles and showed that they link structurally and functionally the two homotopically synchronized posterior parietal areas (primarily BA39), cortical sectors involved in tactile object recognition (17,18,20).…”
Section: Discussionmentioning
confidence: 71%
“…Overall, the findings may result from indirect commissural pathways maintaining bilateral resting-state networks in the absence of direct callosal routes, although with reduced interhemispheric functional connectivity in highly connected hub regions, and possibly also a mechanism involving a common external impetus such as the thalamus enforcing bihemispheric temporal synchrony. The strength of inter-regional functional connectivity was also strikingly more variable across AgCC subjects than controls, which may in part reflect the less consistent organization of their anatomic connectivity, as shown in a recent study of the AgCC structural connectome (Owen et al, 2013a). These initial observations demonstrate the great potential of resting-state fMRI to reveal abnormal function in the malformed brain and thereby also help elucidate the function of the normal human brain.…”
Section: Resultsmentioning
confidence: 87%
“…Hypothesis-driven analyses of structural connectivity of partial AgCC using fiber tractography (Tovar-Moll et al, 2007;Wahl et al, 2009) have shown that some of these individuals have novel heterotopic callosal connections such as sigmoid bundles not seen in the control population. These patterns of connectivity were not seen in all pAgCC subjects, which implies that the aberrant anatomic connectivity of AgCC is individualized, thereby contributing to the relatively variable topology observed across subjects in their structural connectomes (Owen et al, 2013a). The inconsistent organization of the structural connectome in AgCC could provide a basis for the larger inter-subject variation that we observe in the functional connectivity of these subjects versus normal volunteers (Tables 3 and Supplementary Table S2).…”
Section: Relationship Between Functional and Structural Connectivity mentioning
confidence: 88%
See 1 more Smart Citation